Republic of Congo : Review of Performance under the Staff-Monitored Program and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reviews Congo's Performance Under the Staff-Monitored Program (SMP) and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. Improvements in the political environment and an increased focus on economic management since late 2002 have already led to stronger economic growth and lower inflation. The 2004 SMP produced good results. All the program's quantitative budgetary and financial indicators were met. Major progress was made in improving oil sector transparency with the widespread dissemination of information on the Internet, which is particularly noteworthy and exemplary among countries in Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet